PENGARUH KEMAMPUAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAAN KERJA KARYAWAN PADA CV. JAYA ABADI KOTA BIMA - fifi; Kusumayadi, Firmansyah (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
This study aims to determine the employee's work ability has a partially significant effect on employee job satisfaction at CV.jaya Abadi Kota Bima, to find out work motivation has a partially significant effect on employee job satisfaction at CV Jaya Abadi Kota Bima, to determine employee work ability and motivation. work has a significant effect on employee job satisfaction at CV. Jaya Abadi Bima City. Questionnaire research instrument. The scoring technique used in this research questionnaire is a Likert scale. The population in this study were 59 employees at CV. Jaya Abadi Bima City. The sample in this study were 59 permanent employees at CV. Jaya Abadi Bima City with the sampling technique used, namely the saturated sampling technique. Data collection techniques using observation, interviews, questionnaires, documentation. The data analysis technique uses validity test, reliability test, multiple linear regression test, classical assumption test, correlation coefficient test, coefficient of determination, f and t test with the help of SPSS version 21 for windows. The results showed that work ability had no partial effect on employee job satisfaction, work motivation partially affected employee job satisfaction, work ability and work motivation had a simultaneous effect on employee job satisfaction at CV. Jaya Abadi Bima City. Keywords: work ability, work motivation, job satisfaction